High-nuclearity heterometallic clusters with both an anion and a cation sandwiched by planar cluster units: synthesis, structure and properties. Issue 43 (24th October 2017) - Chen, Zilu; Shen, Yanling; Li, Lingling; Zou, Huahong; Fu, Xiaoxiao; Liu, Ziyuan; Wang, Kai; Liang, Fupei
Abstract : We report an unprecedented type of nonadecanuclear heterometallic sandwich structures with both halide anion and alkali metal cation sandwiched by planar nonanuclear clusters. Abstract : To develop high-nuclearity clusters as multi-functional materials, we prepared a new type of sandwich clusters using an anion-templated synthetic strategy. The reactions of (2 R, 3 R )-2, 3-dihydroxybutanedioylbis(salicylidene hydrazone) (H6 L) with [Cu2 (OAc)4 (H2 O)2 ] in the presence of alkali metal halide (NaCl, NaBr, KCl or KBr) provided four high-nuclearity clusters [MCu18 L6 X(C5 H5 N)15 (DMF)3 ]·3DMF·6H2 O (M = Na and X = Cl (1 ); M = Na and X = Br (2 ); M = K and X = Cl (3 ); and M = K and X = Br (4 )). They represent a new type of nanoscale high-nuclearity heterometallic sandwich clusters, in which the halide anion is fully sandwiched by two planar nonanuclear clusters, and the alkali metal ion is half-sandwiched on the top of the upper planar nonanuclear cluster. The experimental magnetic data and simulating results reveal dominant antiferromagnetic interactions between metal ions in these compounds. Their dielectric constants and electric hysteresis loops were also measured.